2020
DOI: 10.1186/s12967-020-02211-4
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-binding protein 1 transcriptionally activates p21 expression via p53-independent mechanism and its frequent reduction associates with poor prognosis in bladder cancer

Abstract: Background: Recent studies have shown that selenium-binding protein 1 (SELENBP1) is significantly down-regulated in a variety of solid tumors. Nevertheless, the clinical relevance of SELENBP1 in human bladder cancer has not been described in any detail, and the molecular mechanism underlying its inhibitory role in cancer cell growth is largely unknown. Methods: SELENBP1 expression levels in tumor tissues and adjacent normal tissues were evaluated using immunoblotting assay. The association of SELENBP1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Epidermal growth factor receptor (EGFR) is a glycoprotein that plays an important role in physiological processes such as proliferation, apoptosis and differentiation of cell by activating the calcium signaling pathway, MAPK signaling pathway and PI3K/AKT signaling pathway ( Carlisle et al., 2007 ). As an important anticancer gene, the inactivation of p53 plays an important role in tumor formation, and increasing studies have found that the p53 plays a crucial role in retarding tumor cell cycle, promoting tumor cell apoptosis and inhibiting tumor angiogenesis ( Bi et al., 2018 ; Li P. et al., 2019 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is a glycoprotein that plays an important role in physiological processes such as proliferation, apoptosis and differentiation of cell by activating the calcium signaling pathway, MAPK signaling pathway and PI3K/AKT signaling pathway ( Carlisle et al., 2007 ). As an important anticancer gene, the inactivation of p53 plays an important role in tumor formation, and increasing studies have found that the p53 plays a crucial role in retarding tumor cell cycle, promoting tumor cell apoptosis and inhibiting tumor angiogenesis ( Bi et al., 2018 ; Li P. et al., 2019 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To give just a few more very recent examples of the protein’s importance, Lee et al have suggested that hepatitis B virus-X-expressing cells, which show markedly decreased SELENBP1 expression, might be one factor in the development of hepatocellular carcinoma caused by HBV infection [ 57 ]. Wang et al have also reported this protein’s novel function in transcriptionally modulating p21 expression through a p53-independent mechanism, with a resulting impact on the G 0 /G 1 phase cell cycle arrest in bladder cancer [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed out that abnormal expression of P53, MutS homologs 2 (MSH2), and tropomyosin-4 (Tm-4) was closely related to the occurrence and metastasis of various cancers. [4][5][6][7][8] P53 is considered to be an important tumor suppressor protein, but reports have pointed out that the P53 gene in many cancer cells will mutate and lose cellular gene repair function. 4 Wang et al 4 It is also well known that inflammation causes many cancers, especially liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of proteomics research technology, the pathogenesis of tumors can be further revealed at the protein level, and tumor‐specific markers and specific antigens can be screened and identified. Recent studies have pointed out that abnormal expression of P53, MutS homologs 2 (MSH2), and tropomyosin‐4 (Tm‐4) was closely related to the occurrence and metastasis of various cancers 4‐8 . P53 is considered to be an important tumor suppressor protein, but reports have pointed out that the P53 gene in many cancer cells will mutate and lose cellular gene repair function 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation